COVID-19 and the risks of coronavirus contamination of the Dental Surgeon in clinical activity (Research, Society and Development, 2021)
The year 2020 will be marked in the world historical context as the year of facing a pandemic caused by an invisible enemy, the virus that transmits COVID-19. It is a family of viruses that causes respiratory infections. The disease was discovered in December 2019 and aerosol transmission is possible when there is a high concentration in relatively closed environments. The aim of the study was to analyze the control and prevention protocols and the risks of contamination by COVID-19 in dental clinical practice. This is a documentary research of protocols, recommendations, guides, manuals and guidelines on COVID-19 prevention and control measures, available in the main databases and websites of government agencies and institutions in the national and international health area. . Seven documents were obtained and included in the research, including technical notes issued by the World Health Organization, Ministry of Health, National Health Surveillance Agency (ANVISA) and Federal Council of Dentistry (CFO). In the analysis of the content of the documents, a framework for data extraction was built. The following variables were observed in the analyzed documents: use of Personal Protective Equipment (Protective masks, cap, gloves, face shields and lab coat), respiratory label guidance, use of antimicrobial mouthwash, recommendation for the use of manual instruments, adequate sterilization of the instrumentals. The rules of distance between professionals and patients, hand hygiene, cleaning and disinfection of the work environment were included in all documents. Knowledge about the ways in which COVID-19 is contagious and the adoption of preventive measures in patient care is important to prevent the spread of the disease.